PENGARUH ROE, EPS ,DER, RISIKO TERHADAP HARGA SAHAM DAN KONSEKUENSINYA TERHADAP RETURN SAHAM (Study Kasus Perusahaan sektor Manufaktur yang terdaftar di Bursa efek indonesia Periode 2015 - 2017) - Yusuf Wijoyanto, 15.05.51.0078; Sudarsi, sri (Students' Journal of Economic and Management, 2019)
This study aims to examine the effect of Return on Equity, Earning per Share (EPS), Debt to Equity Ratio, Risk to stock prices and its consequences for stock returns in manufacturing companies listed in the Indonesia Stock Exchange in 2015 - 2017. This research was conducted with using secondary data. The population in this study is. All manufacturing companies are listed on the Indonesia stock exchange in 2015 - 2017. The samples in this study used a purposive sampling method. The analytical method used in this study is the method of multiple regression analysis. The results of this study prove that ROE has a negative and not significant effect on stock prices, EPS has a positive and significant effect on stock prices, DER has a negative and not significant effect on stock prices, BETA has a negative and significant effect on stock prices and stock prices have a negative and insignificant effect to stock returns. Adjusted R square model 1 is 0.981, this means that 98.1% of the dependent variable can be explained by independent variables and the remaining 0.019% is explained by other variables outside the model while the adjusted R square value in model 2 is -0.003 this means that -0.3% of the dependent variable can be explained by the independent variable and the remaining 1.003% is explained by variables outside the model..